Particle Image Velocimetry of a Swirling Fluidized Bed at Different Blade Angles - Sulaiman, S.A. (Wiley-VCH Verlag, 2016)
The particle motion within a stable swirling operation regime of a fluidized bed is investigated. Particle image velocimetry was used to elaborate the hydrodynamics of multi-sized particles fluidized at different air distributor blade angles. The experimental results revealed that the superficial velocity is the most prominent aspect affecting the hydrodynamics of a swirling fluidized bed (SFB) followed by the bed weight, particle shape, and blade inclination angle. Particles of different sizes and shapes fluidized well in the SFB which emphasizes its superiority over contemporary techniques. The slug-wavy regime in the SFB is promising and has considerable potential, especially for diffusion-controlled reactions and processes in the industry. The particle velocity increased with air flow rate at shallow bed height but decreased with bed weight. Copyright Â© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim